Ultrafast light field tomography for snapshot transient and non-line-of-sight imaging - Xiaohua Feng (Nature Portfolio, 2021)
Speed and 3D capability are often incompatible for non-line-of-sight imaging. Here, the authors introduce ultrafast light field tomography (LIFT) that uses an efficient light field acquisition technique to obtain 3D and time.